Screening and Optimization of Thermo-Tolerant Bacillus Sp. For Amylase Production and Antifungal Activity - Sapkota, Susmita; Khadka, Sujan; Gautam, Aava; Maharjan, Rojina; Shah, Ruby; Dhakal, Sandhya; Panta, Om Prakash; Khanal, Santosh; Poudel, Pramod (Journal of Institute of Science and Technology, 2019)
Amylases are starch degrading enzymes which are produced by plants, animals and microorganisms. Amylases produced by microorganisms have a wide range of industrial applications such as in pharmaceutical, food, textile and paper industries. However, there are still limitations in the isolation of amylase producing microorganisms. The objective of this study was to isolate the potent amylase producing Bacillus sp. from soil samples and evaluate their abilities for inhibiting the aflatoxin producing Aspergillus flavus. In this study, 30 soil samples were used. For the screening and identification of Bacillus strain, morphological and biochemical tests were performed. Iodine assay was done to screen the potent amylase producers. Two parameters (pH and temperature) were used to optimize the cultural conditions for the production of amylase. To determine the total reducing sugar, dinitrosalicylic acid (DNS) assay was used. Altogether 29 colonies were selected and identified as Bacillus spp out of which 16 were selected to determine enzyme activity by cup plate method. Four isolates (DK9, DK10, IM4 and KD7) showing highest amylolytic activities (16 mm, 12 mm, 14 mm and 14 mm zone of hydrolysis) were subjected for further study. Isolate KD7 showed the highest amylolytic activity (0.19 U/mL) compared to other isolates. Maximum amylase production was found at pH 6 and temperature 50° C (0.19 U/mL). Among these 4 isolates, DK9 and KD9 showed strong antagonistic activity against Aspergillus flavus while DK10 and IM4 showed moderate antifungal activities. Thus, the bacterial isolate KD7 was identified as the most potent strain for maximum amylase production.